Validity and reliability of the job content questionnaire in formal and informal jobs in Brazil - de Araújo, Tânia Maria; Karasek, Robert (SJWEH Supplements, 2008)
' ' OBJECTIVES ': 'This study evaluated the job content questionnaire (JCQ) in measuring work psychology aspects with respect to formal and informal jobs in Brazilian occupational groups. ' ' METHODS ': 'A cross-sectional study was carried out in a random sample of 1311 ≥15-year-old residents in the urban area of the city of Feira de Santana, Bahia, Brazil. The Portuguese JCQ version included the recommended 49-item of the original version. The JCQ performance evaluation included descriptive analysis, discriminant analysis, internal consistency, and construct validity. ' ' RESULTS ': 'Averages of the JCQ scales were similar for the formal and informal workers, except for decision authority (formal job: c=31.9; informal jobs: c=34.5). The averages of the Portuguese JCQ scales did not differ substantially from those obtained in other European, North American, and Japanese studies, albeit they were slightly lower in the Brazilian case. In general, Cronbach’s alpha coefficients revealed performance similar to other large-sample studies, showing acceptable internal consistency. The coefficients were relatively similar for formal and informal jobs. Factor analysis revealed high consistency with the theoretical model. ' ' CONCLUSIONS ': 'This is the first study to evaluate JCQ performance comparing formal and informal jobs in a developing country. The job content questionnaire presented a good global performance, and it did not differ substantially from those observed in other studies. These findings suggest that the job content questionnaire can be used in studies carried out in developing countries and in situations in which informal jobs are common.
Keywords: Brazil; decision latitude; demand–control model; formal job; informal job; job; job content; job content questionnaire; occupational stress; psychological demand; psychological distress; reliability; stress; validity